Factors Affecting Entrepreneurial Intention to Startup: Evidence among Nepalese Business Students (The Lumbini Journal of Business and Economics, 2026)
Purpose: Entrepreneurship is one of the significant factors for the development of the economy, employment opportunities, and innovation, especially for developing countries such as Nepal. Thus, the purpose of this study is to explore the entrepreneurial intentions of Nepalese business students in the Kathmandu Valley.Methods: The study is based on the Theory of Planned Behavior, and the research method used is an explanatory research method. The study is based on a sample size of 403 business students of the Kathmandu Valley. Nonprobability convenience sampling is used to collect the data. Descriptive and inferential analysis is used to analyze the collected data. Preliminary analysis is done using Microsoft Excel software, and structural equation modeling is done using SmartPLS 4.1 software to test the proposed model.Results: From the results obtained, it can be noted that the inclination towards starting a business is higher among the male students who are currently employed in the private sector. Entrepreneurial skills (β = 0.319, P < 0.001), innovation (β = 0.175, p = 0.010), peer influence (β = 0.175, p = 0.006), and risk-taking propensity (β = −0.130, p = 0.042)  entrepreneurial intention. On the other hand, the aspects of self-motivation and family support do not show a significant influence on the students’ decision to start a business. The challenges are mainly due to the constraints in funding, risk-taking ability, entrepreneurial skills, and family support.Conclusion: The study concludes that entrepreneurial intentions among business students in Nepal are significantly influenced by entrepreneurial skills, innovation capabilities, peer influences, and risk-taking propensities. These factors can be enhanced through institutional support and policy interventions to boost youth entrepreneurship in Nepal.